Building religious moderation through islamic religious education: a study of high school teachers in Banten Indonesia - Yudin, Fithri; Nugraha, Enung; Syarifudin, Efi; Wasehudin, Wasehudin (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2025)
Religious moderation has become an urgent issue in Indonesia’s educational context, particularly in fostering tolerance and preventing radicalism among students. Schools play a crucial role in shaping students’ perspectives on religious diversity, with Islamic Religious Education (IRE) teachers serving as key agents in instilling moderation values. However, the implementation of religious moderation in schools faces various challenges, including curriculum constraints, sociocultural influences, and students’ diverse backgrounds. This study aims to analyze the specific strategies employed by IRE teachers in fostering religious moderation, the challenges they encounter, and the impact of their efforts on students. Using a qualitative research method with a social phenomenological approach, data were collected through in-depth interviews, classroom observations, and document analysis involving IRE teachers and students in a senior high school in Banten, Indonesia. Thematic analysis was conducted to identify recurring patterns and key themes related to religious moderation practices. The findings indicate that IRE teachers implement religious moderation through interactive teaching methods, interfaith dialogues, and role-modeling behaviors that emphasize tolerance and balance. However, challenges such as limited institutional support, resistance from certain groups, and a lack of comprehensive training hinder the effectiveness of these efforts. Despite these obstacles, the study highlights the positive influence of IRE teachers in fostering an inclusive and harmonious school environment. The implications of this research suggest the need for more structured teacher training programs, curriculum adjustments to integrate religious moderation effectively, and policy support from educational institutions. These findings contribute to the broader discourse on religious moderation and provide practical recommendations for improving Islamic education in diverse learning environments.